How are government public relations addressed in existing and future research? - Bachri, Achmad Syahrully; Muqsith, Munadhil Abdul; Tayibnafis, Radita Gora (PRofesi Humas, 2026)
Background: Several studies have investigated Government Public Relations (GPR) over the last few decades. However, very little exhaustive research has been conducted on this issue so far. Purpose: The study aims to provide a comprehensive review of the literature and a bibliometric analysis of GPR based on existing empirical research. Methods: The study employed a Systematic Literature Review, searching for the phrase “Government Public Relations” in article titles, abstracts, and keywords in the Scopus database, yielding 126 articles from 1976 to 2025. The evaluation was done on October 19, 2025. The raw data were analyzed bibliometrically using VOSviewer. Results: The research shows that GPR has experienced remarkable worldwide expansion, with the greatest concentration in the United States and Indonesia. This growth is driven primarily by digital transformation, global crises, demands for democratization, the complexity of global issues, and the professionalization of GPR. Conclusion: The GPR sector in emerging countries is still under-researched. Research works in the past have primarily dealt with advanced countries, for example, the United States and South Korea. Future research should address the needs of developing countries, particularly Africa, Latin America, and Central Asia. The paper argues that there are five essential qualities of effective GPR: transparency, accountability, public participation, responsiveness, and two-way communication. The paper also analyses the conceptual framework of GPR. Implications: The consequences for the sustainable administration and development of government organizations and for ensuring their adherence to GPR principles.